The The Relationship Of Nurse’s Effective Communication Patterns To Anxiety Level Among Carcinoma Patients Undergoing External Radiotherapy At Adi Husada Cancer Center Surabaya - Dwi Uswatun Sholikhah; Vendi Eko Kurniawan; Fakhrun Nisa' Fiddaroini (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Introduction: Anxiety is a common problem experience by cancer patient undergoing external radiotherapy causes physical and psychological factors. Anxiety can worsen the patient’s condition because anxiety reduce immune system by lower activity of T lymphocyte cells as natural killer cells, so it can make increase the growth of malignant cells. Treatment for cancer patients is often only focused on physical factors, while the patient’s psychological factor is sometimes neglected. One way that can be used to reduce the patient's psychological anxiety is use communication effectively. However, the relationship of nurse’s effective communication patterns to anxiety level among carcinoma patients undergoing external radiations therapy is not yet clear. Methods: A correlation analytic approach with cross sectional design to analyze the relationship between nurse communication and patient anxiety level. This research was conducted on 40 respondents carcinoma undergoing external radiations therapy on August-September 2021. Subjects were chosen using purposive sampling. Result: The data were analyzed using spearman rank test. The data shows not significant figures or numbers p-value= 0.329 > ? (0.05). Implementing effective communication among patients carcinoma undergoing radiotherapy can’t reduce the patient's anxiety level. Discussion: Effective communication can help clients clarify the burden of feelings and thoughts, get the information needed, feeling heard, feeling cared so that it can reduce the client's anxiety. But in this study, factor can affect anxiety level in patient cancer undergoing radiotherapy are age of patients, background education, cancer stage, length of cancer, social support, financing, sources of information and role change.